The Use of Cooperative Learning Method Type of Listening Team to Increase Students’ Learning Outcomes in Social Studies at 4th Grade of Elementary School - Usmaedi Usmaedi; Bunyamin Maftuh; Hamdan Hamdan; Siti Nurbayani K; Puji Siswanto (Universitas Majalengka, 2022)
Cooperative learning (CL) has a pivotal role in the teaching and learning process to achieve better academic performance using an attractive teaching trait. This study aims at investigating the use of the Cooperative Learning method type listening team, knowing the students’ response and their learning outcomes in a social science subject. The study is conducted at one of the Public Elementary schools in Rangkasbitung. Classroom Action Research was employed in this study. The Cooperative Learning method type of listening team was conducted within 2 cycles. There are 22 students as the subjects of the current study. The data of the study were collected using two research instruments, they are observation and written test. The results of the study revealed that the activities of both teachers and students in the learning process using a Cooperative Learning type listening team improve students’ learning outcomes. The level of students’ learning mastery in the pre-cycle was 24%, in cycle 1 was 48% and in cycle 2 the passing grade reached 79%. While, the activities of teachers and students increased by 75% in the use of cooperative learning methods of the previous team listening and learning outcomes of students also increased, and 75% of the number of students achieved the standard of minimum completeness of mastery learning predetermined. Based on the data findings, it can be highlighted that the CL method type listening team is an effective method to improve both students’ learning outcomes and their activities during the class.